Growth and gas exchange in white pitaya under different concentrations of potassium and calcium (Revista Ciência Agronômica, 2023)
Agriculture in Brazil has improved at a fast pace in recent years, given the growing demand for quality andthe need for new products. In this respect, white pitaya [Hylocereus undatus (Haw.) Britton & Rose] has become a feasiblealternative for Northeast farmers. The limiting factors include a small amount of data on plant mineral nutrition and cropgrowth (phenology). Therefore, this study goal was to evaluate the effect of different concentrations of potassium (K) andcalcium (Ca) on crop development and gas exchange in white pitaya grown in the coastal region of the state of Ceará, inBrazil. Sixteen treatments with three repetitions were organized in a completely randomized block design and a 4 ´ 4 factorialarrangement. Treatments consisted of various concentrations of K (0; 125; 250 and 375 mg dm-3) and Ca (0, 53, 106, and 159mg dm-3). Biometric characteristics and gas exchange were determined after 270 and 240 days of treatment, respectively. Formorphometric characteristics, the most significant nutrient combination was 250 mg dm-3 of K and 159 mg dm-3 of Ca. Netphotosynthesis was higher at the dose of 125 mg dm-3 of K and 0 mg dm-3 of Ca. Our results indicate that, for the environmentalconditions under which the test was conducted, an optimum nutrient combination for the analyzed variables was 250 mg dm-3K and 159 mg dm-3 Ca.